Bahasa Indonesia Pada Era Globalisasi (kedudukan, fungsi, Pembinaan, dan Pengembangan) - Masnur Muslich (Bumi Aksara, 2015)
Bahasa Indonesia Pada Era Globalisasi (kedudukan, fungsi, Pembinaan, dan Pengembangan)